Circadian Variation in Arterial Blood Pressure and Glaucomatous Optic Neuropathy—A Systematic Review and Meta-Analysis - Andrea Bowe; M. Grünig; Jens Schubert; Münevver Demir; Vera Hoffmann; Fabian Kütting; A Pelc; Hans‐Michael Steffen (2015)
Epidemiological studies have led to equivocal results concerning the role of arterial blood pressure as a risk factor for the development of glaucomatous damage and progressive visual field loss in glaucoma has been attributed to low nighttime blood pressure, especially when oral antihypertensives have been combined with beta-blocking eyedrops. In order to answer the question whether nocturnal blood pressure or blood pressure dip during ambulatory blood pressure monitoring are associated with progressive visual field loss we performed a systematic review and meta-analysis of studies in patients with primary open-angle glaucoma and normal tension glaucoma. After searching MEDLINE, the Cochrane Library, and EMBASE, only 5 studies could be found reporting information on the method of ambulatory blood pressure measurements, separate data for daytime and nighttime blood pressure, definition of nocturnal blood pressure dip, and assessment of visual fields over a period of at least 2 years. There was no difference in mean systolic or diastolic diurnal and nocturnal blood pressure between patients with or without progressive visual field loss. The odds ratio for deteriorating visual fields over 2 years with nocturnal dips >10% in systolic or diastolic blood pressure was 3.32 (1.84–6.00) and 2.09 (1.20–3.64), respectively. Data allowing a separate analysis of over-dipping were not available. Nocturnal blood pressure fall is a risk factor for progressive visual field loss in glaucoma. However, prospective studies are needed to define a tolerable degree of dipping. Antihypertensive therapy in glaucomatous patients should be controlled with ambulatory blood pressure monitoring.